Pengaruh Edukasi Silma + Fr Terhadap Pengetahuan Mengenai Pencegahan dan Perawatan Hiperbilirubin Pada Ibu Yang Menjelang Kelahiran di Rs Grha Permata Ibu Depok Tahun 2025 - Siti Silmawati Sulaiha; Yani Handayani (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Hyperbilirubinemia in newborns is a common condition that can potentially cause complications if not treated properly. Mothers' lack of knowledge prior to giving birth about the prevention and treatment of hyperbilirubinemia can increase the risk of delayed treatment, thus requiring effective health education. This study aims to determine the effect of S.I.L.M.A + FR education on mothers' knowledge about the prevention and treatment of hyperbilirubinemia at Graha Permata Ibu Hospital in Depok in 2025. This study used a quantitative method with a pre-experimental one-group pre-test and post-test design. The study sample consisted of 16 respondents selected using total sampling technique, using a questionnaire instrument on knowledge about hyperbilirubinemia. The results showed that before education, mothers' knowledge was in the “fair” category at 62.5% and “poor” at 31.3%, while after education, there was an increase in knowledge to the ‘fair’ category at 68.8% and “good” at 31.3%. The results of the paired t-test showed a significance value of 0.0001, which means that there was an increase in mothers' knowledge after being given S.I.L.M.A + FR education. This education has an effect on increasing mothers' knowledge about the prevention and treatment of hyperbilirubinemia in newborns and can be applied as a promotive and preventive measure in maternal and child health services.